Logos i niewiasta u początków Kościoła. Szkic do eklezjogenezy - Napiórkowski, Andrzej (Analecta Cracoviensia, 2011)
The article attempts to determine the origins of the Church. The author maintains that the formation of the Church should be perceived as a concept coming from God the Father. The Church originated at the time of the Fall of Adam and Eve. A resulting breach of human communion with God triggered an immediate response on the part of God. It was His divine purpose that the communion be re-established, but on a different level. This was achieved in the biblical Eden. The Eternal Logos has not only fulfilled the creative, but also the redemptive function. A Woman is permanently inscribed into the origins of the Church. In her we may see Mary, the Mother of Christ and the Mother of Church.